Field reaction of cassava genotypes to anthranose, bacterial blight, cassava mosaic disease and their effects on yield - Fokunang, C.N.; Ikotun, T.; Dixon, Alfred G.O.; Akem, C.N. (2000)
Thirteen cassava genotypes were evaluated at the International Institute of Tropical Agriculture, Ibadan, Nigeria for anthracnose (CAD), bacterial blight (CBB) and cassava mosaic disease (CMD) incidence and severity, and their effects on yield, for three consecutive planting seasons. There were significant differences (P<0.05) in CAD, CBB and CMD incidence and severity amongst the cassava genotypes across the planting seasons. Yield assessment showed significant differences (P<0.05) in storage root number, plant stand, root fresh weight and dry matter content among the cassava genotypes. There was no significant variation in tuber rot among the genotypes, and 80% of the genotypes did not show any tuber root rot when harvested 12 months after planting. CBB and CAD incidences were significantly and positively correlated (r=0.43), whereas CBB and CMD incidences were not significantly correlated (r=0.03). CAD and CMD incidence and severity were highly correlated (r=0.82 and r=0.76, respectively). CBB incidence was negatively correlated with storage root weight and fresh root tuber number (r=-0.45 and r=-0.48, respectively). CMD severity showed a significant negative correlation with storage root weight (r=0.44). Cassava genotypes TMS 30001, 30211 and 88/01087 showed a stable resistance over 3 planting seasons to CAD, CBB and CMD.